Synergistic Effect of Zinc Oxide Nanoparticles and Moringa oleifera Leaf Extract Alleviates Cadmium Toxicity in Linum usitatissimum: Antioxidants and Physiochemical Studies - Ramzan, Musarrat; Ayub, Fazila; Shah, Anis Ali; Naz, Gul; Shah, Adnan Noor; Malik, Aqsa; Sardar, Rehana; Telesiński, Arkadiusz; Kalaji, Hazem M.; Dessoky, Eldessoky S.; Elgawad, Hamada Abd (Frontiers in Plant Science, 2022)
Among heavy metals, cadmium (Cd) is one of the toxic metal which significantly reduces growth of plants even at low concentration. Cadmium interacts with various plant mechanisms at the physiological and antioxidant levels, resulting in decreased plant growth. Current research was conducted to exploit the potential of synergistic application of zinc oxide nanoparticles (ZnO NPs) and Moringa oleifera leaf extract in mitigation of Cd stress in Linseed (Linum usitatissimum L.) plants. The main purpose of this study was to look at impacts of M. oleifera leaf extract and zinc oxide nanoparticles (MZnO-NPs) on Cd exposed Linseed plants. Cadmium concentrations in root and shoot of Linseed plants decreased after administration of MZnO–NPs, according to our findings. Growth parameters of plants, antioxidant system, and physiochemical parameters all decreased as the external Cd level increased. The administration of MZnO–NPs to the Cd-stressed Linseed plant, on the other hand, caused a significant increase in these factors. Furthermore, the antioxidative enzymes superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX) exhibited a considerable increase in activity when MZnO–NPs were applied to Cd-stressed seedlings. The introduction of MZnO-NPs lowered the levels of malondialdehyde (MDA) and hydrogen peroxide (H2O2) in the Linseed plant grown in Cd-toxic conditions. The NPs decreased electrolyte leakage (EL) in Cd-stressed Linseed leaves and roots. It was concluded that synergistic application of ZnO NPs and M. oleifera leaf extract alleviated Cd stress in Linseed plants through enhanced activity of antioxidant enzymes. It is proposed that role of MZnO-NPs may be evaluated for mitigation of numerous abiotic stresses.